Age (40Ar/39Ar) data and major and trace element and isotope (Sr, Nd, Pb, Hf) data of igneous rocks recovered from the King extquotesingles Trough area in the North Atlantic during METEOR cruise M168 - Jörg Geldmacher; Antje Dürkefälden; Folkmar Hauff; Dieter Garbe-Schönberg; Daniel A Frick; Brian Jicha (PANGAEA, 2025)
Major and certain trace element data determined on fused glass pellets of igneous whole rock samples by XRF and by Electron Microprobe on fresh volcanic glass fragments. Comprehensive trace element analyses from a subset of these samples carried out by (solution) inductively coupled plasma mass spectrometry (ICP-MS) and by laser ablation ICP-MS (glass fragments). Radiogenic (Sr, Nd, Pb, Hf) isotope ratios by utilizing a thermal ionization mass spectrometer (Sr, Nd, Pb isotopes) and a Multi-Collector (MC)-ICP-MS (Hf isotopes). Information on data quality and international rock standard measurements are included in this data publication. 40Ar/39Ar geochronology was carried out on groundmass and plagioclase separates by using a Nu Instruments Noblesse mass spectrometer. Analytical data tables, age spectra and inverse isochrons plots are included in this data publication.